The Influence of Trump’s Leadership Style on American Foreign Policy During Covid-19 Pandemic - Simin, Sharon Pricilia Mareta; Rahman, Muhammad Sigit Andhi (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
Scholars argue that Trump’s character and experience influence American foreign policy during a crisis such as the COVID-19 pandemic. His controversial policy can be seen from his reopening of America agenda at a time when the situation was not conducive yet, the rejection to join COVAX, confrontational behavior toward WHO and China, the reduction of international engagement with the European Union to address COVID-19. This article examines how Trump’s leadership style influenced American foreign policy during the COVID-19 pandemic in 2020. It mainly uses psychobiography and content analysis as complementary methodologies. This article found that Trump is a predominant leader with a more goal-driven style. He is a leader who likes to challenge constraints, is closed to information, and is achievement-motivated, with an expansionist type. His personalities of high level of dominance, high self-confidence, emotional, ambitious and aggressiveness shaped his foreign policy to be inconsistent and unpredictable during the pandemic. Keywords: American Foreign Policy, COVID-19 Pandemic, Donald Trump, Leadership Style